Penggunaan metode demonstrasi Problem Based Learning (PBL) untuk meningkatkan keterampilan menulis teks prosedur - Jimat Susilo; Veronika Endang Wahyuni (BAHASTRA, 2019)
This study aims to describe the improvement of procedure text writing in class XI MIPA 1 Yogyakarta State Senior High School 6 using the Problem Based Learning (PBL) demonstration method. The method of this research is classroom action research. The research subjects were XI MIPA 1 Yogyakarta State Senior High School totaling 35 students. This study consisted of two cycles. Data collection techniques used were observation, interview, procedure text writing test, and documentation. Data analysis using qualitative and quantitative descriptive analysis techniques. Validity of data with validity (democratic, process, dialogic) and triangulation. The results showed that the demonstration method of Problem Based Learning can improve the ability to write procedural texts in terms of processes and results in class XI MIPA 1 Yogyakarta 6 Senior High School Improving the quality of the process can be seen from the role of teachers and students who experienced a significant increase in the implementation of learning. This is indicated by the emergence of a positive response through the attitude of cooperation and enthusiasm shown by students, as well as conducive conditions of learning. Process improvement ultimately has a positive impact on increasing yield. The increase in results can be seen from the increase in the score of the procedure text of students from the first cycle to the second cycle. The average score at the time of the action was 68.14 on average in the first cycle of 68.57, and the average in the second cycle was 80.64. The increase in the average score from pre-action to cycle II is 12.05.